2018
DOI: 10.5194/acp-18-4617-2018
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of long-range transport biomass burning emissions to the Himalayas: insights from high-resolution aerosol mass spectrometry

Abstract: Abstract. An intensive field measurement was conducted at a remote, background, high-altitude site (Qomolangma Station, QOMS, 4276 m a.s.l.) in the northern Himalayas, using an Aerodyne high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) along with other collocated instruments. The field measurement was performed from 12 April to 12 May 2016 to chemically characterize the high time-resolved submicron particulate matter (PM 1 ) and obtain the dynamic processes (emissions, transport, and chemic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(87 citation statements)
references
References 84 publications
8
79
0
Order By: Relevance
“…Aerosol sources for these two sites Each arrow corresponds to the addition of a particular functional group to an aliphatic carbon and the percentage number indicate the data points in each region to the total data points. Based on satellite monitoring and in situ observations (Kumar et al, 2011;Zhang et al, 2018), biomass burning has been identified as the major source of OA in the southern TP, while anthropogenic emissions (coal combustion and fossil fuel usage) are the major source of OA in the northern TP (Figure 12). The plot of DBE vs. n C .…”
Section: Potential Aerosol Sources and Chemical Processes In These Twmentioning
confidence: 99%
See 3 more Smart Citations
“…Aerosol sources for these two sites Each arrow corresponds to the addition of a particular functional group to an aliphatic carbon and the percentage number indicate the data points in each region to the total data points. Based on satellite monitoring and in situ observations (Kumar et al, 2011;Zhang et al, 2018), biomass burning has been identified as the major source of OA in the southern TP, while anthropogenic emissions (coal combustion and fossil fuel usage) are the major source of OA in the northern TP (Figure 12). The plot of DBE vs. n C .…”
Section: Potential Aerosol Sources and Chemical Processes In These Twmentioning
confidence: 99%
“…could be generally determined by air mass trajectory analysis which show that the air mass to WLG were all from the inland of northwest of China with about 50% from the source at short distance (100-200 km), while they were dominantly from northwest of India with long distance (up to 1,000 km) ( Figure S5). Based on satellite monitoring and in situ observations (Kumar et al, 2011;Zhang et al, 2018), biomass burning has been identified as the major source of OA in the southern TP, while anthropogenic emissions (coal combustion and fossil fuel usage) are the major source of OA in the northern TP (Figure 12). This is determined by the energy structure and distribution of natural resources in the countries adjacent to the northern and southern part of the TP region.…”
Section: Potential Aerosol Sources and Chemical Processes In These Twmentioning
confidence: 99%
See 2 more Smart Citations
“…Qomolangma from Apr. 12 to May 12, 2016 using a suit of 83 instruments (Zhang et al, 2018b), and the instruments used in this study includes a HR-ToF-84 AMS (Aerodyne Research Inc., Billerica, MA, USA) for 5-min size-resolved chemical 85 compositions (organics, sulfate, nitrate, ammonium, and chloride) of non-refractory submicron 86 particulate matter (NR-PM 1 ) and a photoacoustic extinctionmeter (PAX, DMT Inc., Boulder, 87 CO, USA) for BC mass concentration. The QOMS observatory locates at a remote site with 88 sparse local residents and anthropogenic activities around it, except for a high way for the 89 tourism to the west about 500 m. The tourists are normally increased from June each year due to 90 the warmer weather during summer.…”
Section: Aerosol Sampling 81mentioning
confidence: 99%